2023
DOI: 10.1111/anae.15960
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid in total knee arthroplasty

Abstract: Twitter: @DocCRBailey When we administer any medication, it should be safe, effective and affordable. Tranexamic acid (TXA) was first introduced as a therapeutic drug in the early 1960s [1], so we now have 60 years' experience in its use. It is a synthetic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Open access with high bleeding, such as cardiac surgery, major orthopaedic surgery and traumatic bleeding. [12][13][14] These studies have confirmed the feasibility and tolerability of using TXA. 15 Furthermore, TXA has been found to possess anti-inflammatory properties.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 54%
“…Open access with high bleeding, such as cardiac surgery, major orthopaedic surgery and traumatic bleeding. [12][13][14] These studies have confirmed the feasibility and tolerability of using TXA. 15 Furthermore, TXA has been found to possess anti-inflammatory properties.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 54%
“…The application of TXA is mainly divided into oral, intravenous drip, water light needle injection, etc. Studies have shown that the onset time of intravenous drip therapy for melasma is faster than that of oral administration [9] . Some studies have also shown that the effect of water light needle injection of TXA+glutathione compound drug is better than that of intravenous injection of TXA [10] .…”
Section: Resultsmentioning
confidence: 99%
“…There are also inconsistent results in terms of transfusion rates and drainage in previous articles, with [3][4][5], which may be related to whether tranexamic acid was used intraoperatively. Tranexamic acid reduces bleeding and transfusion requirements in the perioperative period [23,24].The transfusion rate in the study by Dikmen İ et al [4] was partly due to a decrease in the use of tranexamic acid.In addition,there is a difference in the results of drainage ow between Dikmen İ et al and Batmaz AG et al [3,5]. We compared them and found that the time of drainage tube removal was different, and since drainage ow increases with time, it is closely related to the time of removal and also to the use of perioperative anticoagulants [25,26].…”
Section: Discussionmentioning
confidence: 96%